(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article examines the physical and chemical properties of spent zinc catalysts and the process of processing 30% nitric acid. Used zinc catalysts contain at least 95% zinc oxide. The treatment process was carried out in 30% nitric acid in a cycle closed at a temperature of 85-950C, pH within 3-4, by mixing the solution for 5 hours. The mass fraction of Zn(NO3)2 in the solution obtained according to the above parameters is higher than 400 g/dm 3 , and the density of the liquid phase after decomposition varies from 1.312 gr/cm3 to 1.273 gr/cm3 , depending on the pH value of the medium and temperature. The viscosity under these conditions varies from 0.02 sPa to 0.008 sPa.